Comparison of the world and european records in the 100m dash by a quasi-physical model - Barbosa, T. M.; Forte, P.; Marinho, D. A.; Reis, V. M. (Procedia Engineering, 2016)
The aim was to employ a quasi-physical model to analyse the performance and biomechanics of the World and European records at the 100m dash in Athletics. At the time of this research, the World record was hold by Usain Bolt (Jamaica) with 9.58s and the European record 9.86s by Francis Obikwelu (Portugal). The analysis of the performance employs a quasi-physical model that feature the drive, maintenance, velocity and drag terms. Obikwelu showed a slower start (drive term) and Bolt a lower rate of deceleration over the race (propulsive term). The velocity and drag terms were higher for Bolt. Correcting the race time for a hypothetical null wind speed, Bolt's time would have been 9.62s (i.e. a 0.04s impairment) and 9.89s for Obikwelu (i.e. a 0.03s impairment).